Поховання культурного кола Бабине з астрагалами - Литвиненко, Р.О. (My University, 2005)
R. Litvinenko. Burials of a Babino Cultural Circle With Pasterns The present article is devoted to research of burials of Babino cultural circle into which funeral stock included a bones of joints of the hoofed animals legs, frequently named pasterns (in Latin — Talus, in Ukrainian and in Russian — astragal). The all-round statistical data and the analysis of archaeological contexts of pasterns finds in burials are submitted. It was possible to reveal local features of use of pasterns in funeral ritual for Dnepr-Don Babino and Dnepr-Prut Babino cultures. The conclusion that, at least, a part from pasterns in burials performed a semiotics meaning of ritual knuckle bones or fortunetelling bones is made. Practice of use of pasterns in a funeral ceremony of tribes of Babino culture has been inherited by the population of Timber-Grave cultures. In the long term researches it is necessary to carry out the similar analysis of sources of Catacomb cultures, and then to lead the retrospective comparison of the data on cultures of a middle and late Bronze Age of Northern Black Sea region.